Identifying residual transmission of lymphatic filariasis after mass drug administration: Comparing school-based versus community-based surveillance - American Samoa, 2016. - Meru Sheel; Sarah Sheridan; Katherine Gass; Kimberly Won; Saipale Fuimaono; Martyn Kirk; Amor Gonzales; Shannon M Hedtke; Patricia M Graves; Colleen L Lau (PLoS Neglected Tropical Diseases)
Introduction Under the Global Programme to Eliminate Lymphatic Filariasis (LF), American Samoa conducted seven rounds of mass drug administration (MDA) from 2000-2006. The World Health Organization recommends systematic post-MDA surveillance using Transmission Assessment Surveys (TAS) for epidemiological assessment of recent LF transmission. We compared the effectiveness of two survey designs for post-MDA surveillance: a school-based survey of children aged 6-7 years, and a community-based survey targeting people aged ≥8 years. Methods In 2016, we conducted a systematic school-based TAS in all elementary schools (N = 29) and a cluster survey in 28 villages on the two main islands of American Samoa. We collected information on demographics and risk factors for infection using electronic questionnaires, and recorded geo-locations of schools and households. Blood samples were collected to test for circulating filarial antigen (CFA) using the Alere Filariasis Test Strip. For those who tested positive, we prepared slides for microscopic examination of microfilaria and provided treatment. Descriptive statistics were performed for questionnaire variables. Data were weighted and adjusted to account for sampling design and sex for both surveys, and for age in the community survey. Results The school-based TAS (n = 1143) identified nine antigen-positive children and found an overall adjusted CFA prevalence of 0.7% (95% CI: 0.3-1.8). Of the nine positive children, we identified one microfilariaemic 7-year-old child. The community-based survey (n = 2507, 711 households) identified 102 antigen-positive people, and estimated an overall adjusted CFA prevalence of 6.2% (95% CI: 4.5-8.6). Adjusted village-level prevalence ranged from 0-47.1%. CFA prevalence increased with age and was higher in males. Of 86 antigen-positive community members from whom slides were prepared, 22 (25.6%) were microfilaraemic. School-based TAS had limited sensitivity (range 0-23.8%) and negative predictive value (range 25-83.3%) but had high specificity (range 83.3-100%) and positive predictive value (range 0-100%) for identifying villages with ongoing transmission. Conclusions American Samoa failed the school-based TAS in 2016, and the community-based survey identified higher than expected numbers of antigen-positive people. School-based TAS was logistically simpler and enabled sampling of a larger proportion of the target population, but the results did not provide a good indication of the overall CFA prevalence in older age groups and was not sensitive at identifying foci of ongoing transmission. The community-based survey, although operationally more challenging, identified antigen-positive individuals of all ages, and foci of high antigen prevalence. Both surveys confirmed recrudescence of LF transmission.